Construção e validação de aplicativo educativo para prevenção da incontinência urinária em mulheres após o parto - Saboia, Dayana Maia (2017)
Pelvic Floor Dysfunctions are common clinical conditions affecting women of multiple age groups and Urinary Incontinence (UI) is the most prevalent among them. It is estimated that one in four women has some type of urinary loss. During postpartum, higher rates have been described, estimated between 27 and 33%. Obstetric factors and advancing age have been established as some of the risk factors. However, the literature reveals that UI can be avoided in most cases and points to Pelvic Floor Muscle Training as a recommended and positive measure. Despite this, there is a lack of awareness among women about prevention. In this context, health education mediated by an educational technology emerges as a strategy to enable individuals to adopt positive behaviors in relation to their health. Therefore, this study aimed to construct and validate an educational app as a technology to prevent urinary incontinence in postpartum women. It was a study of technological development, which consists of building and developing software and other technological strategies. App development was made in four stages: modeling, navigation design, abstract interface design and implementation. The modeling step was supported by the systematic review of effective postpartum interventions to prevent urinary incontinence. Also this stage featured the topics to be addressed in the application and the way in which they were presented. During the navigation project stage, menus, images and data organization were elaborated. App appearance was developed in collaboration with a system programmer during the abstract interface phase. The last step featured the app deploy to the Android and iOS platforms. In the validation process, twenty-two specialists (eleven health specialists and eleven from information technology / computing / communication areas) and twenty-two patients were invited to evaluate the educational app in terms of content and appearance. The app was validated with a CVI of 0.93 in the assessment of health specialists and agreement percentage ranging from 81.8% to 100% in expert assessment and target audience for an appearance. In this step, points of adjustment were identified in relation to the app’s content and interface that were considered and corrected. Once the requested modifications have been made, the app is currently validated for use as an educational technology to prevent urinary incontinence in postpartum women.